Effect of strut orientation on the microstructure heterogeneities in AlSi10Mg lattices processed by selective laser melting. (December 2017) - Delroisse, Pauline; Jacques, Pascal J.; Maire, Eric; Rigo, Olivier; Simar, Aude
Abstract: The microstructure heterogeneities are compared between inclined and vertical struts of AlSi10Mg lattices processed by Selective Laser Melting. While the vertical struts present a fully dense homogenous microstructure, large levels of porosities and heterogeneous microstructure are present in inclined struts, particularly a much larger level of porosities in the bottom part of the strut compared to the top part. These differences are due to a larger time spent at high temperature for the bottom zone of the strut. A solutionizing and aging heat treatment homogenizes the microstructure but leads to a minor softening due to eutectic spheroidization. Graphical abstract: